Comparative evaluation of pseudonym-based anonymisation techniques for connected autonomous vehicles (CAVs) - Sheik, Al Tariq; Liu, Jia; Dianati, Mehrdad; Maple, Carsten (Frontiers in Future Transportation, 2025)
The technical requirements for securing safety-related applications in connected autonomous vehicles (CAVs) include security (e.g., authentication, integrity, non-repudiation depending on the specific applications), privacy (e.g., anonymity and unlinkability) and computing efficiency of the solutions designed to address security and privacy aspects. Several cryptographic techniques have been considered in the literature to meet these technical requirements. A notable category of these techniques is often referred to as pseudonym schemes in the context of CAVs, which aim to address security and privacy simultaneously. This paper provides an overview of the state-of-the-art research on pseudonym techniques for CAVs, including a comparative evaluation of their performance in the context of two representative safety-related CAV applications: Cooperative positioning and intersection collision avoidance. This study aims to guide the effective adoption of such schemes for various applications in CAVs. In this paper, three main categories of pseudonym schemes are considered: public key schemes, identity-based signatures, and group signatures. We compare these schemes with respect to security and privacy requirements as identified for several CAV applications. We also implement several representative pseudonym schemes in each category to evaluate their processing efficiency for signing and verifying messages used in CAV applications to provide insight into their applicability for CAV applications.